Proximate Composition and Mineral Content of Some Cameroonian Traditional Sauc es Prepared from Red Sorrel Leaves (H ibiscus sabdariffa L.) - Ponka, Roger; Tabot Tambe, Sylvia; Lina Tchatchoua Nankap, Eveline; Fokou, Elie (Current Nutrition & Food Science, 2016)
Protein-energy malnutrition and micronutrient deficiencies continue to be a major health burden in Cameroon. Sauces made with leafy vegetables are good sources of proteins and micronutrients. This study was conducted to determine the proximate composition and the mineral content of some Cameroonian traditional sauces prepared from red sorrel leaves. A survey of the cooking methods and consumption was conducted in 120 households that accepted to take part in the study in the city of Garoua, in the North region of Cameroon. The proximate composition was determined by the standard Association of Official Analytical Chemists methods and minerals by atomic absorption spectrophotometry. From the survey, eleven traditional sauces were prepared from fresh or dried leaves of red sorrel in the city of Garoua. Basing on the compositional analyses carried out in this study, recipe 5 is the best source of protein, fat, dietary fiber (6.18, 13.75 and 1.99 g /100 g edible portion, respectively). Appreciable levels of minerals were recorded in all the sauces. But recipe 5 also had the highest calcium, sodium, iron and copper contents (321.99, 425.30, 5.67 and 0.29 mg /100 g edible portion, respectively). Consumption of each recipe (100 g) by children of 1-2 years old would meet 12.26-47.51%, 14.30-45.82%, 4.20-10.48%, 0.82-6.54% and 3.87-13.51% of their daily recommended intakes, respectively for protein, fat, dietary fibre, carbohydrates and energy. On the other hand, consumption of each recipe (100 g) by children of 1-2 years old would meet 8.58-64.40%, 19.16-67.34%, 16.48-42.53%, 2.66-22.68%, 21.22-80.95%, 5.55-37.67%, 39.66-86.18% and 14.94-37.72% of their daily recommended intake, respectively for calcium, magnesium, sodium, potassium, iron, zinc, copper and manganese. Malnutrition in this population can therefore be reduced through the consumption of these sauces.
Keywords: red sorrel leaves